Modernization Efforts Undertaken by the Nepali Army - Bhattarai, Ajaya (The Journal of Knowledge and Innovation, 2023)
One of the nation's oldest organizations is the Army of Nepal. The development of Nepal's modern nation has been greatly aided by the armed forces. The ultimate responsibility for protecting, maintaining, and safeguarding the nation's independence has fallen on the Nepali Army. Science and technology are used for the development of the armed forces in China and India. Against this backdrop, Nepal experiences cyber-attacks, environmental degradation, pandemics, and ethnic, racial, or religious conflicts, among other things. The people of Nepal have faith in the Nepal Army since they are involved in various service-related activities. However, Nepal has a poor economy, it lags far behind in the modernization of the national army. Based on the study, the current strength and technical resources available to the Nepali Army to handle different types of challenges have been investigated. In this article, the Nepali Army's struggles to adapt to a new political system and the initiatives it has made to modernize itself are mostly discussed. With the changing nature of modern warfare, tactics, and situations, some changes have been necessary for Nepal's Army on the front of training, habitats, equipment, and technology. This article also discusses the achievements of Gehendra Shamsher (1871–1906), a firearms designer, inventor, and high-ranking officer of the Nepalese Army, as a role model for Nepal's modernization efforts. After Gehendra Shamsher, the Nepali Army has undertaken several modernization initiatives. The main objective of this paper is to discuss some modernization efforts done by the Nepal Army using science and technology. The material is taken from various sources, such as Tribhuvan University's Central Library in Kirtipur, the Army Central Library, the Military Museum in Kathmandu, and national and international literature."